2018
DOI: 10.1080/0142159x.2018.1460656
|View full text |Cite
|
Sign up to set email alerts
|

Online interprofessional education facilitation: A scoping review

Abstract: While the included studies provide some insight into the nature of online IPE facilitation, future research is needed to better understand facilitator contributions, and the facilitation experience and associated outcomes, both relating to synchronous and asynchronous online environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 31 publications
1
39
0
1
Order By: Relevance
“…Current pandemic reality aside, over the past several years it has become increasingly popular to deliver IPE in an online learning format (S. M. Evans et al, 2019), although a review of the literature from the past five years showed that, there are relatively few program evaluation studies of online IPE programs and associated student learning outcomes. In one study, authors evaluated the pilot of a large asynchronous online IPE course in integrative medicine and demonstrated that it is possible to effectively deliver online curriculum to interprofessional students in geographically separated locations (Brooks et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Current pandemic reality aside, over the past several years it has become increasingly popular to deliver IPE in an online learning format (S. M. Evans et al, 2019), although a review of the literature from the past five years showed that, there are relatively few program evaluation studies of online IPE programs and associated student learning outcomes. In one study, authors evaluated the pilot of a large asynchronous online IPE course in integrative medicine and demonstrated that it is possible to effectively deliver online curriculum to interprofessional students in geographically separated locations (Brooks et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is largely due to the complexities of delivering IPE, including the timetabling and logistical issues associated with the delivery of face-to-face IPE activities. 11,12 In addition, there is often a preference for individuals to work within their established silos. [13][14][15] There is a paucity of pedagogical practices that are studentcentered, provide active learning with content that is simultaneously relevant to the learning needs of different professions, and are designed for implementation on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…This is largely due to the complexities of delivering IPE, including the timetabling and logistical issues associated with the delivery of face-to-face IPE activities. 11 , 12 In addition, there is often a preference for individuals to work within their established silos. 13 - 15 …”
Section: Introductionmentioning
confidence: 99%
“…There is also potential to explore online learning delivery options to mitigate scheduling, geographical location and varying student number challenges. Although a newer area in IPL literature, there is some evidence to suggest that online IPL facilitation may be a feasible approach (Evans et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%